(untitled) (Research, Society and Development, 2023)
This study aimed to identify the clinical management of pulmonary thromboembolism in the literature. The methodology selected for carrying out this research is an integrative literature review study, where a survey of data was carried out in the scientific bases: LILACS and SCIELO. The results showed that the clinical management starts after the diagnosis, initially, the diagnosis and confirmation of this condition for treatment represent a challenge for physicians who need to monitor this suspicion and perform tests in a timely manner. The importance of investigating the patient’s clinical history and considering the risk factors for embolism is emphasized. Clinical management of pulmonary embolism must be performed in the hospital, and clinical response rates vary according to the size of the embolism, the affected area, and the delay in diagnosis. In the hospital, the main measures are to provide oxygen, analgesics to control pain, and anticoagulants to prevent existing clots from progressing and to prevent new clots from forming.